The post-2007 crises and Europe's place in the global economy - Richard Pomfret (Center for Social and Economic Research (CASE), 2012)
What is often abbreviated to GFC included three distinct crises: the 2007-8 North Atlantic financial crisis, a 2008-9 global economic crisis and public finance crises which became increasingly focussed on the eurozone in 2010-12. The relative weight of emerging market economies in the global economy, which had been increasing for several decades, grew even more rapidly in 2008-11 as the economies of the USA and Europe faltered, and other open economies recovered rapidly from the global economic crisis. This poses challenges for global economic governance, although there are constraints on Asia being a more assertive force. For the EU the greater dangers are, first, that if EU leaders see their economies as victims of a GFC then they will fail to address their economies' own shortcomings, and, second, that preoccupation with internal crises will distract EU leaders from rising to the challenges and opportunities associated with the evolving multipolar global economy.
Keywords: G01; O53; F40; 330; Financial crises; Global economy; Multipolar world; Finanzkrise; Finanzmarktregulierung; Internationale Wirtschaft; Europa